Employer wage subsidies and wages in Germany: empirical evidence from individual data - Gesine Stephan (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2010)
In Germany, targeted wage subsidies to employers are an important instrument of active labor market policy. This paper compares the wages of individuals taking up a subsidized job with those of otherwise similar individuals who found an unsubsidized job, combining propensity score matching with a differences-in-differences strategy. The results indicate for the short-run that subsidized jobs are not associated with gains or losses regarding daily wages. Nonetheless, because subsequent employment rates of subsidized persons are higher on average, we find a positive relationship between cumulated wages and subsidization.
Keywords: J31; J38; J58; 330; Eingliederungszuschuss - Auswirkungen; Lohnkostenzuschuss - Erfolgskontrolle; arbeitsmarktpolitische Maßnahme; Lohnhöhe; Beschäftigungsdauer